(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Induction motors can be designed for powers ranging from small to considerable. Several key parameters must be considered during the design process. In addition to critical motor design parameters, there are also design parameters that are not taken into consideration and are usually taken as a fixed or average value. One of these parameters is the λ (lambda) parameter, which represents the ratio of the package length to the pole pitch. This parameter is typically specified in design books and appears to be a subject that researchers do not often study. In this study, a 7.5 kW, 3-phase squirrel-cage induction motor has been designed using the lambda value to fill the gap in the literature. The primary motivation of this study is to demonstrate how the lambda value influences the dimensions of the motor and its impact on the performance and magnetic performance of the motor. For this purpose, analytical and 2D modeling have been performed using Rmxprt and Ansys Maxwell software for motor analysis. Performance and magnetic analyses were performed. According to the results obtained, it is concluded that the lambda coefficient, which is not very important in the design process, is a very effective parameter in motor design.